Risk Factors for Intradialytic Hypotension in Chronic Kidney Disease Patients Undergoing Hemodialysis - Faizah Ramadhani; Fitri Mailani; Devia Putri Lenggogeni (Fakultas Keperawatan Universitas Andalas, 2025)
Intradialytic hypotension (IDH) is one of the most common complications of hemodialysis therapy experienced by hemodialysis patients, with a prevalence of 8–40%. IDH carries important clinical consequences, including reduced dialysis adequacy and interruption of treatment sessions. Several factors are known increase the occurrence of IDH. This study aimed to identify risk factors influencing the occurrence of intradialytic hypotension in patients with chronic kidney disease undergoing hemodialysis. This study used a quantitative method with a cross-sectional design. The study was conducted in the hemodialysis unit of a government hospital in Padang City. The sampling technique was purposive sampling with a sample size of 104 respondents with inclusion and exclusion criteria, between April and May 2025. Data analysis used the Chi-Square test and the Mann-Whitney U test. The results showed that gender, dialysate temperature, and meals during hemodialysis were not associated with intradialytic hypotension (p > 0.05). However, hemoglobin and Interdialytic Weight Gain (IDWG) were related to the occurrence of intradialytic hypotension (p < 0.05). Based on the results of this study, nurses can monitor and evaluate anemia status and IDWG, which can influence the incidence of intradialytic hypotension. The role of nurses in improving dietary compliance and fluid restriction is crucial in preventing intradialytic hypotension.